MicroRNA-199a-3p and microRNA-34a regulate apoptosis in human osteosarcoma cells. Issue 4 (6th August 2014) - Tian, Ye; Zhang, Ying-Ze; Chen, Wei
Abstract : miRNAs (microRNAs) are small non-coding RNAs [18–25 nt (nucleotides)] that regulate gene expression mainly through affecting post-transcriptional modification. Osteosarcoma is an aggressive sarcoma of the bone characterized by a high level of genetic instability and recurrent DNA deletions and amplifications. miRNAs play an important role in cancer cell growth and migration; however, the potential roles of miRNAs in osteosarcoma remain largely uncharacterized. In this paper, miR-199a and miR-34a were discussed the mechanisms of apoptosis using miRNA mimics in human osteosarcoma cells. The results demonstrated that miR-199a and miR-34a could induce the apoptosis of human osteosarcoma cells via p53 signalling pathway.